Assessment of the contribution of CFH and chromosome 10q26 AMD susceptibility loci in a Russian population isolate. Issue 5 (18th October 2006) - Fisher, Sheila A; Rivera, Andrea; Fritsche, Lars G; Babadjanova, Gulja; Petrov, Sergey; Weber, Bernhard H F
Abstract : Background/aims: A strong association has been confirmed between age-related macular degeneration (AMD) and variants at two independent loci including Tyr402His in the complement factor H ( CFH ) on 1q32 and Ser69Ala at LOC387715, a hypothetical gene on chromosome 10q26. The contribution of both loci to AMD was investigated in an isolated north-west Russian population. Methods: Together with a PLEKHA1 variant at 10q26, the CFH Tyr402His and LOC387715 Ser69Ala polymorphisms were genotyped in 155 patients with AMD and 151 age-matched controls. χ 2 and Mantel–Haenszel (M–H) score tests were used to test for association. Sex-adjusted ORs were calculated. Results: The frequency of the Tyr402His C allele was significantly higher in patients with AMD compared with controls (pM–H = 0.0035). The increased risk observed in patients homozygous for the C allele (ORHOM = 2.71, 95% CI 1.25 to 5.90) in this indigenous Russian population was considerably lower than that observed in previous western Caucasian populations. A significant increase in the frequency of the LOC387715 variant was observed in patients with late-stage AMD compared with controls (pM–H = 0.007), with a homozygous OR of 3.47 (95% CI 1.01 to 11.9), although this association was not seen with early-stage AMD. Conclusion: The CFH gene contributes to AMD in this Russian population, although the risk conferred is considerably lower in this population than that found in other Western populations. A contribution of LOC387715 to disease in this population is also likely to be of weak effect.